Cloning and expression of 3-hydroxybutyrate dehydrogenase gene from locally isolated Pseudomonas sp. - Nik Mahmod, Nik Azmi; Mohd Illias, Rosli; Syed Muhammad, Syed Annuar Fauad; H. D., Habib Abdullah Fikri; S., Wan Nor Azlinda; Lau, S. Y. (Universiti Malaysia Sabah, 2003)
The 3-HBDH gene from Pseudomonas sp. was amplified, cloned, and sequenced. The deduced amino acid sequence was highly matched with 3-HBDH sequences in DDBJ/GenBank/EMBL. But Pseudomonas sp. 3-HBDH was lack of the C-terminal region found in mammalian enzymes containing a lipid-binding domain that is important for the 3-HBDH's activity. The E-coli XL1 blue cells transformed with the resultant plasmid, pBDH-1 showed 3-HBDH's activity. The E. coli XL1 Blue cells transformed with resultant plasmid, pBDH-1 showed 3-HBDH's activity. The nucleotide sequence of recombinant pBDH-1 indicate functional oligomers composed of subunits of 225 amino acid with a calculated Mr of 26, 855 Da and proved on SDS-PAGE. Ammonium sulfate farctionation resulted in low yield of the enzyme but its activity was comparably high with other 3-HBDHs. The recombinant enzyme showed a broad range of stability with respect to pH and temperature.